(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The investment budget represents a stage of the investment decision in service units, and the preparation and implementation needs to be a complement of the same planning part, because the planning does not end with the development of the plan, but includes a follow-up implementation, so it has to be effective and efficient oversight of the estimates and procedures for disbursement of funds approved for investment projects, The problem with research in that local governments suffer from the presence of Allkaat and problems facing the implementation of the investment budget projects due to the adoption budget items which can not be measured the efficiency of the performance of these units of government by, and shortcomings in the control procedures for investment projects from the other side, as well as the lack of treatment Local governments offenses installed in regulatory reports. The importance of this research of the importance of the role played by local governments and increasing the funds and projects managed by those governments in the implementation of the investment budget, which constitute a high proportion of the state budget allocations and the impact of such projects in the national economy the size of projects. The researcher sought to indicate the role and responsibility of external oversight bodies in monitoring the implementation of the investment budget for local governments projects so as to ensure the proper implementation of these projects, and to shed light on the state of confusion and lack of implementation of the investment budget for local governments and evaluate external oversight procedures on the process of implementation of those budget, and to study the possibility of the application of some mechanisms such as the application of auditing programs and submit periodic reports that lead to the lifting of the regulatory action to reduce the level of confusion and deficiencies in the work of local governments and reduce waste in public funds. Was based on research on assumptions integration of the work of foreign equipment and the use of effective monitoring and efficient in the implementation of the investment budget projects, and the commitment of local governments to address the observations and irregularities installed in regulatory reports help to improve the performance of those governments and reduce waste in public funds and contribute to the proper implementation of these projects and ensure usage Optimization of available resources and achieve economic and social development goals. The researcher reached a set of conclusions most important, the presence of investment financial plan based on scientific grounds will contribute well in achieving the goals and Todev funds for the purpose of the programs established, with the need for the availability of a number of necessary to measure the efficiency of the work of these programs are indicators, and the negative impact of the lack of attention to the reports prepared by regulators and weak accountability to the local government has led to complacency to provide answers and explanations necessary for those regulatory reporting procedures, and thus impacts on local government performance, and was the key recommendations, the need to adopt scientific bases studied in the development of the investment plan and determine the programs and objectives that a government unit seeks to achieve , with the need to develop the necessary performance measurement efficiency in the implementation of projects and programs of investment indicators, and the need for effective follow-up reports to regulators and take appropriate corrective action and to ensure non-recurrence of such violations in other projects.